2009
DOI: 10.1542/peds.2008-2697
|View full text |Cite
|
Sign up to set email alerts
|

Early Weight Gain Predicts Retinopathy in Preterm Infants: New, Simple, Efficient Approach to Screening

Abstract: The weight, insulin-like growth factor, neonatal retinopathy of prematurity algorithm detected early 100% of infants who developed retinopathy of prematurity requiring treatment and correctly predicted the majority who did not require treatment. With this simple postnatal evaluation, costly stressful eye examinations can be markedly reduced (approximately 75% of infants). In addition, early identification of children at risk may lead to the initiation of interventions and possibly prevent sight-threatening ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
224
3
15

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 236 publications
(250 citation statements)
references
References 36 publications
8
224
3
15
Order By: Relevance
“…Recently, clinical prediction models to early identify patients in risk of ROP were presented. WINROP [29][30][31] and PINT-ROP 32 were presented using postnatal longitudinal weight gain measurements. ROPScore, by the other hand, uses the BW and the weight measured at completed 6 weeks of life as weighted values in the final calculation of the score.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, clinical prediction models to early identify patients in risk of ROP were presented. WINROP [29][30][31] and PINT-ROP 32 were presented using postnatal longitudinal weight gain measurements. ROPScore, by the other hand, uses the BW and the weight measured at completed 6 weeks of life as weighted values in the final calculation of the score.…”
Section: Discussionmentioning
confidence: 99%
“…9 Later it was shown that only serial weight measurement part of WINROP algorithm, excluding IGF-1 measurements, can also predict severe ROP requiring treatment with 100% sensitivity. 10 This algorithm was validated in a different cohort of infants in Sweden and USA. 11,15 The first three studies we have mentioned were focused on weight gain during the first 6 weeks of life.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] Recent data suggest that one of the strongest predictors of ROP is poor weight gain during the first weeks of life. [7][8][9][10][11] In this prospective study, we aimed to evaluate relative weight gain by 2 weeks intervals up to 6 weeks after birth in order to predict the development of ROP requiring treatment among very low birth weight (VLBW) infants.…”
Section: Introductionmentioning
confidence: 99%
“…Its variable specificity and poor positive predictive value in studies (table) 98,100,[121][122][123][124][125][126] suggest that the algorithm should be used in addition to conventional screening guidelines. WINROP does not currently include infants with a gestational age at birth of more than 32 weeks.…”
Section: Classification and Screeningmentioning
confidence: 99%